New insights into Chlamydia pathogenesis: Role of leukemia inhibitory factor - Wang, Jun; Wang, Katherine (Frontiers in Cellular and Infection Microbiology, 2022)
Chlamydia trachomatis (Ct) is the leading cause of bacterial sexually transmitted infections worldwide. Since the symptoms of Ct infection are often subtle or absent, most people are unaware of their infection until they are tested or develop severe complications such as infertility. The unresolved chronic inflammation is believed to be the primary culprit of Ct-associated tissue damage, which stimulates aberrant production of cytokines, chemokines, and growth factors, as well as dysregulated tissue influx of innate and adaptive immune cells. Leukemia inhibitory factor (LIF), a member of IL-6 cytokine family, is one of the cytokines induced by Ct infection, but its role in Ct pathogenesis is unclear. In this article, we review the biology of LIF and LIF receptor (LIFR)-mediated signaling pathways, summarize the physiological role of LIF in the reproductive system, and discuss the impact of LIF in acute and chronic inflammatory conditions and its implication in Ct pathogenesis. Available evidence supports a novel role of LIF in Ct pathogenesis. Although LIF is produced for the purpose of maintaining epithelial homeostasis and tissue repair upon Ct infection, LIF/LIFR-mediated signaling, particularly prolonged strong signaling, gradually transforms the microenvironment of the fallopian tube via alteration of the fate of epithelial cells and the cellular composition of epithelium. The harmful transformation of epithelium might be a key process leading to an enhanced risk of infertility, ectopic pregnancy and cancer.